Trapezoidal PWM scheme for voltage gain inverter - Harikrishna Naraboyana; I. Kumaraswamy (International Journal of Applied Power Engineering (IJAPE), 2026)
The trapezoidal modulating wave-based high voltage gain 9-level inverter (HVG9LI) addresses significant difficulties related to the growing usage of capacitors, DC sources, and semiconductor switches. The proposed HVG9LI generates a nine-level resultant voltage with few components, exhibiting the capacity to double the output voltage gain. Furthermore, the HVG9LI utilizes a trapezoidal modulating wave and variable frequency carrier (TM-VFC) pulse width modulation method to increase the resulting voltage and enhance the voltage output quality. The performance and practicability of the HVG9LI with TM-VFC are evaluated across several modulation techniques and indices implemented by using MATLAB/SIMULINK and tested experimentally.